Effects of Temperature and Nutrient Supply on Resource Allocation, Photosynthetic Strategy, and Metabolic Rates of Synechococcus sp. Issue 3 (26th March 2020) - Fernández‐González, Cristina; Pérez‐Lorenzo, María; Pratt, Nicola; Moore, C. Mark; Bibby, Thomas S.; Marañón, Emilio
Abstract : Temperature and nutrient supply are key factors that control phytoplankton ecophysiology, but their role is commonly investigated in isolation. Their combined effect on resource allocation, photosynthetic strategy, and metabolism remains poorly understood. To characterize the photosynthetic strategy and resource allocation under different conditions, we analyzed the responses of a marine cyanobacterium ( Synechococcus PCC 7002) to multiple combinations of temperature and nutrient supply. We measured the abundance of proteins involved in the dark (RuBisCO, rbc L) and light (Photosystem II, psbA) photosynthetic reactions, the content of chlorophyll a, carbon and nitrogen, and the rates of photosynthesis, respiration, and growth. We found that rbc L and psbA abundance increased with nutrient supply, whereas a temperature‐induced increase in psbA occurred only in nutrient‐replete treatments. Low temperature and abundant nutrients caused increased RuBisCO abundance, a pattern we observed also in natural phytoplankton assemblages across a wide latitudinal range. Photosynthesis and respiration increased with temperature only under nutrient‐sufficient conditions. These results suggest that nutrient supply exerts a stronger effect than temperature upon both photosynthetic protein abundance and metabolic rates in Synechococcus sp. and that the temperature effect on photosynthetic physiology and metabolism is nutrient dependent. The preferential resource allocation into the light instead of the dark reactions of photosynthesis as temperature rises is likely related to the different temperature dependence of dark‐reaction enzymatic rates versus photochemistry. These findings contribute to our understanding of the strategies for photosynthetic energy allocation in phytoplankton inhabiting contrasting environments.